Environmental Carrying Capacity and Load Capacity Determination System for Ecosystem Services Management - Hery Saputra; Tjahjo Tri Hartono; Budi Susetyo; Almyanti Ningrum (Universitas Ibn Khaldun Bogor, 2024)
Sustainable development is a key focus of Indonesia’s policy framework, as mandated by Law No. 32 of 2009 and Government Regulation No. 46 of 2016, which emphasize integrating Environmental Carrying Capacity and Load Capacity (CCLC) into development planning. This study identifies challenges in current CCLC assessments, including limited data accuracy and inconsistent methodologies. To address these issues, an innovative Environmental CCLC Determination System is proposed, integrating ecosystem services and advanced spatial modeling. The research methodology combines a comprehensive literature review and expert interviews to analyze existing practices and design the system. The proposed system incorporates decision support tools and spatial data analysis to provide a scientifically grounded, unbiased, and accessible framework for policymakers. Initial implementation will involve collaboration with academic experts, universities, and local governments, particularly in Bogor Regency and Bogor City. The system is expected to significantly enhance regional planning and environmental stewardship by the end of the 2025–2030 development period, aligning policies with sustainable development goals.